The Avant Rehabilitation Program and Cerebrolysin for Treatment of Post-Stroke Dysphagia: A Case Report - Hien, Nguyen Minh (J Med Life, 2019)
Dysphagia is recorded in approximately a third of ischemic stroke patients and is associated with malnutrition, aspiration, and pneumonia. We report a case study that assessed dysphagia (GUSS, Gugging Swallowing Screen), paralysis (MRC, Medical Research Council), and disability (mRS, modified Rankin Scale) in the AVANT program (Austrian Vietnamese Advancement Neurorehabilitation Treatment) - a collaboration program between Vietnam and Austria to standardize and systemize neurorehabilitation after stroke practice in Vietnam.